Hubungan insomnia dengan depresi pada lanjut usia di Sesetan Kecamatan Denpasar Selatan Tahun 2017 - Luh Putu Mettary Yasoda Gera; Anak Ayu Sri Wahyuni; IGA Indah Ardani (DiscoverSys Inc., 2019)
Introduction: Insomnia is difficulty falling or maintaining sleep that often experienced by general population. Insomnia mostly experienced by elderly woman, people with low education and low economy and in people who have chronic disease. Insomnia is risk factor from psychiatric disorder especially depression. Insomnia increase the risk in depression development. Depression is disorder on personal, interpersonal and social that affecting general population. The purpose of this study is to know the relationship between insomnia and depression in elderly.Method: The type of this study is analytical observational (Cross-sectional) study with amount of sample 32 respondents that conducted in Banjar Gaduh and Banjar Tengah in Sesetan, South Denpasar District in elderly in 2017. This study is using the primary data obtained through questionnaire and interview (GDS and ISI) and analyzed through SPSS 21.0.Result: This study found that from 32 respondents experienced insomnia (50%), not experienced Insomnia (50%), experienced depression (28.1%) and no experience depression (71.9%) and relationship insomnia with depression on eldery obtained value p < 0.05 . The R-square value indicates value of 0.673 which means that role variable independent in explain variable dependent only of 67.3%, could be concluded that still there are 24.6% other variables outside the research variables that affect insomnia.Conclusion: There were a significant relationships between depression and insomnia.